A Comparative Study of Oxytocin & Misoprostol in Active Management of Third Stage of Labour - Ansari, N; Das, CR (Journal of Nepalgunj Medical College, 2015)
Introduction: The third stage of labour is the period which follows the completed delivery of the foetus and consists of delivery of the placenta and its attached membranes. Aims and objectives: Comparison of oxytocin & misoprostol in active management of third stage of labour. Material and Methods: This is a comparative cross-sectional study was conducted in Nepalgunj Medical College Teaching Hospital, Kohalpur from March 2013 to March 2014. Group A - Oxytocin 10 IU IV bolus in 100 patients and Group B - Misoprostol 600 micro gram rectally. The collected were subjected to statistical analysis using SPSS 15. Results: After active management with bolus oxytocin, the blood loss was grossly reduced being 40-100ml in 84% cases and only 7% had blood loss more than 100ml. blood loss between 200-300ml were only 6% and only 3% had PPH, after misoprostol 80% of cases had blood loss within 40 – 100 ml., 6% cases had blood loss within 100 – 200 ml. and larger amount of blood loss i.e. between 200 – 300 ml. was observed in 7% cases, in 3% cases blood loss was between 300 – 400 ml. and 4% of women in this group had PPH. Conclusion: There was no statistically significant difference in the efficacy of oxytocin and misoprostol in reducing amount of blood loss and duration of labour rd in 3 stage of labour. Journal of Nepalgunj Medical College Vol.12(1) 2014: 22-24